2015
DOI: 10.2967/jnumed.114.153007
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction-Incorporated Respiratory Motion Correction in Clinical Simultaneous PET/MR Imaging for Oncology Applications

Abstract: Simultaneous PET and MR imaging is a promising new technique allowing the fusion of functional (PET) and anatomic/functional (MR) information. In the thoracic-abdominal regions, respiratory motion is a major challenge leading to reduced quantitative and qualitative image accuracy. Correction methodologies include the use of gated frames that lead to low signal-to-noise ratio considering the associated low statistics. More advanced correction approaches, previously developed for PET/CT imaging, consist of eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 32 publications
1
37
0
Order By: Relevance
“…Figure 1 illustrates the diagram for the RTA and the MCIR methods for PET motion correction. Several phantom and patient studies 3538 compared both approaches based on the OSEM image reconstruction and regularized reconstruction, and reported that the MCIR approach yielded better motion-corrected images as compared with the RTA approach.…”
Section: Motion Correction In Pet Reconstructionmentioning
confidence: 99%
“…Figure 1 illustrates the diagram for the RTA and the MCIR methods for PET motion correction. Several phantom and patient studies 3538 compared both approaches based on the OSEM image reconstruction and regularized reconstruction, and reported that the MCIR approach yielded better motion-corrected images as compared with the RTA approach.…”
Section: Motion Correction In Pet Reconstructionmentioning
confidence: 99%
“…Several studies have shown that respiratory motion information obtained with MR can strongly improve the quality of PET images (16,17). Furthermore, tagged MR images have been used for cardiac motion correction in phantom experiments (18).…”
mentioning
confidence: 99%
“…Preliminary results using computer simulations and a deformable phantom appear promising. Further investigation reported in more recent studies demonstrated the full potential of MRI-guided motion correction and its feasibility in clinical and research settings [73]- [75].…”
Section: Mri-guided Motion Compensation In Pet/mrimentioning
confidence: 96%